Fluorometric High-Throughput Screening Assay for Secreted Phospholipases A2 Using Phospholipid Vesicles. (August 2016) - Ewing, Heather; Fernández-Vega, Virneliz; Spicer, Timothy P.; Chase, Peter; Brown, Steven; Scampavia, Louis; Roush, William R.; Riley, Sean; Rosen, Hugh; Hodder, Peter; Lambeau, Gerard; Gelb, Michael H.
There is interest in developing inhibitors of human group III secreted phospholipase A2 (hGIII-sPLA2) because this enzyme plays a role in mast cell maturation. There are no potent inhibitors for hGIII-sPLA2 reported to date, so we adapted a fluorescence-based enzyme activity monitoring method to a high-throughput screening format. We opted to use an assay based on phospholipid substrate present in phospholipid vesicles since this matrix more closely resembles the natural substrate of hGIII-sPLA2, as opposed to phospholipid/detergent mixed micelles. The substrate is a phospholipid analogue containing BODIPY fluorophores dispersed as a minor component in vesicles of nonfluorescent phospholipids. Action of hGIII-sPLA2 liberates a free fatty acid from the phospholipid, leading to a reduction in quenching of the fluorophore and hence an increase in fluorescence. The assay uses optical detection in a 1536-well plate format with an excitation wavelength far away from the UV range so as to minimize false-positive library hits that result from quenching of the fluorescence. The high-throughput screen was successfully carried out on a library of 370, 276 small molecules. Several hits were discovered, and data have been uploaded to PubChem. This study describes the first high-throughput optical screening assay for secreted phospholipase A2 inhibitors based on a phospholipid vesicle substrate.